Experience of nursing and health education for a breast-feeding woman with rhagades of the nipple treated with egg yolk oil external application (蛋黄油外涂治疗哺乳期乳头皲裂1例的护理及健康宣教体会) - ZHONG Shuang (仲爽); JIA Ruijing (贾瑞晶); CHEN Hong (陈宏) (中西医结合护理)
This paper summarized the experience of nursing and health education for a breast-feeding woman with rhagades of the nipple treated with egg yolk oil external application. Based on the pain and degree of rhagades evaluation, the external application of egg yolk oil , as well as health education, was carried out to improve wound healing and enable patient to establish and sustain exclusive breastfeeding. (本文总结1例采用蛋黄油外涂治疗哺乳期乳头皲裂患者的护理及健康宣教经验。护理人员完善护理评估, 采用外涂蛋黄油治疗乳头皲裂, 同时配合健康宣教, 有助于促进创面愈合, 对保证母乳喂养的正常进行有积极意义。)